Awesome Aggregations - Constible, Juanita; Lee, Richard E., Jr (The Science teacher (National Science Teachers Association), 2006)
Insects are a natural choice for studying behavioral ecology in the classroom--they are easy to obtain, maintain, and manipulate. Unlike competition and predation, however, the concept of group living does not translate well to small-scale experiments involving only a few individuals. How can inquiry be used to examine why animals live in groups? The answer is to use models, which are more feasible than working with hundreds of test subjects. This article describes a Standards-based directed inquiry into overwintering biology and behavioral ecology titled "Awesome Aggregations" that high school students can carry out with models of monarch butterflies to examine their adaptive value. (Contains 5 figures.)